Information services today an introduction - Hirsh, Sandra 1965- (Lanham Rowman & Littlefield, 2022)
"This book demonstrates the ever-changing landscape of information services today and the need to re-evaluate curriculum, competency training, professional development, and lifelong learning in order to stay abreast of current trends and issues, and more significantly, remain competent to address the changing user needs of the information community"--
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: Information resources; Information services; Libraries and electronic publishing; Library administration; Library users; Public services (Libraries); Librarians -- Effect of technological innovations on; Libraries -- Aims and objectives; Libraries -- Information technology; Library science -- Vocational guidance